PENGARUH RETURN ON EQUITY DAN DEBT TO EQUITY RATIO TERHADAP NILAI PERUSAHAAN DENGAN HARGA SAHAM SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Jurnal Akuntansi Barelang (JURNAL AKUNTANSI BARELANG, 2017)
This study was conducted to fulfill the duty of a lecturer in the Tri Dharma College. This research was conducted to see the effect variabel return on equity and debt to equity ratio of the value of the company stock price as a moderating variable. The value of the company is one of the indicators to be able to see whether or not the company's financial condition. With the high value of the company, this means the company's financial performance has been good so being targeted by potential investors to infuse funds into the company in the form of shares. The share price can also be used as an indicator to see healthy whether the financial condition of the company, the stock price is high indicates the company is able to obtain high profits that the company shares were being targeted by investors or prospective investors, with the number of investors or prospective investors interested in investing in companies , then the stock price will also increase. Rising stock prices also will increase the value of the company. This research was conducted at the Indonesian Stock Exchange, which is the object of this research is the company's Property and Real Estate listed on the Indonesia Stock Exchange. Results of this research is the return on equity significantly influence the value of the company, debt to equity ratio significantly influence the value of the company, return on equity and debt to equity ratio simultaneously significant effect on the value of the company, the stock price does not affect the relationship between return on equity the value of the company, and the stock price does not affect the relationship between the debt to equity ratio of the value of the company. The coefficient of determination of 55.8%. This means, the variable return on equity and debt to equity ratio was able to explain the value of the company amounted to 55.8%, while the remaining 44.2% is explained by other factors not described in this study